2012
DOI: 10.1186/1471-2458-12-1054
|View full text |Cite
|
Sign up to set email alerts
|

Occupational health risks of pathologists - results from a nationwide online questionnaire in Switzerland

Abstract: BackgroundPathologists are highly trained medical professionals who play an essential part in the diagnosis and therapy planning of malignancies and inflammatory diseases. Their work is associated with potential health hazards including injuries involving infectious human tissue, chemicals which are assumed to be carcinogenic or long periods of microscope and computer work. This study aimed to provide the first comprehensive assessment of the health situation of pathologists in Switzerland.MethodsPathologists … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
55
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(67 citation statements)
references
References 49 publications
7
55
5
Order By: Relevance
“…The overall one-year prevalence of musculoskeletal symptoms among the laboratory workers at anybody site was 52.04% (Table 2), which was lower than that of nurses (from 60% to 93%) (Trinkoff et Moreover, shoulder was the most affected body site (33.5%) ( Table 2) among the participants which could be related to strained hand and arm movements done by the laboratory worker during their working hours (Mani and Gerr, 2000).But this was in disagreement with many studies done on laboratory workers in which neck formed the most prevalent site of work related musculoskeletal symptoms (Rahimi et al, 2010 andFritzsche et al, 2012).…”
Section: Discussioncontrasting
confidence: 49%
“…The overall one-year prevalence of musculoskeletal symptoms among the laboratory workers at anybody site was 52.04% (Table 2), which was lower than that of nurses (from 60% to 93%) (Trinkoff et Moreover, shoulder was the most affected body site (33.5%) ( Table 2) among the participants which could be related to strained hand and arm movements done by the laboratory worker during their working hours (Mani and Gerr, 2000).But this was in disagreement with many studies done on laboratory workers in which neck formed the most prevalent site of work related musculoskeletal symptoms (Rahimi et al, 2010 andFritzsche et al, 2012).…”
Section: Discussioncontrasting
confidence: 49%
“…In our study, we found that chair with lower back support or with adjustable heights were preferred for viewing. Despite this preference, still the participants had WMSDs which may be because other working conditions like neutral position and working hours were not followed by them [10]. Our results showed that nearly 50% of the subjects were aware about the (Centres for Disease Control and Prevention) CDC guidelines regarding the permissible usage of microscope in a day to be comfortable to the operator on a long run.…”
Section: Results and Observationsmentioning
confidence: 65%
“…A number of highly trained medical professionals and technicians may help doctors to make decisions and save lives [3]. One such group comprises those who use microscope as a tool of investigation [3].…”
Section: Introductionmentioning
confidence: 99%